Design, synthesis and evaluation of an NLRP3 inhibitor diazirine photoaffinity probe. Issue 19 (7th May 2020) - Hill, James R.; Coll, Rebecca C.; Schroder, Kate; Robertson, Avril A.B.
Graphical abstract: Highlights: Synthesis of TPD-950-Br, a trifluoromethyl phenyl diazirine-analogue of MCC950. TPD-950-Br is a potent NLRP3 inhibitor, IC50  = 164 nM. TPD-950-Br cross-links with methanol when UV irradiated. TPD-950-Br is synthesised via a Sandmeyer-style sulfochlorination. Abstract: The NLRP3 inhibitor MCC950/CRID3 ameliorates a remarkable number of inflammatory disorders in animal models. Herein we describe a trifluoromethyl phenyl diazirine (TPD) photoaffinity probe, called TPD-950-Br, to probe the molecular interactions of MCC950. We show that TPD-950-Br covalently captures proximal species upon photo-activation and inhibits IL-1β production in an NLRP3 inhibitor assay.